Menilik kebijakan pengolahan limbah B3 fasilitas pelayanan kesehatan selama pandemi COVID-19 di Provinsi Jawa Barat - Pricillia Putri Ervian Sitompul (Universitas Riau, 2021)
Managing hazardous medical waste in COVID-19 era has its own challenges. Acknowledging such challenges, the provincial Government of West Java suggested every health care facility in West Java to collaborate with PT Jasa Medivest or other companies that provide waste management services. Commonly, they use incinerator machines as their main tools to demolish the hazardous medical waste. Although it is a commonly used method to demolish medical waste, there are several issues that need to be marked. Therefore, this study aims to observe and analyze the advantages and disadvantages of the suggestion made by the Provincial Government from the perspective of environmental and economic sustainability. This study also proposes several alternative methods to overcome the problems by reflecting on methods that other countries had successfully conducted. This study uses a normative legal research method, in which secondary data are obtained from library research. The data obtained are analyzed and explained using descriptive methods. The results revealed that in the terms of environmental sustainability, the use of incineration method has the potential to perpetuate air pollution. Meanwhile, in terms of financial efficiency, collaborating with PT Jasa Medivest or other companies that provide waste management services incurs a fairly high cost. Hence, it is necessary to evaluate and consider other waste management options.